CAMPUR KODE DALAM KEGIATAN MENCERIAKAN KEMBALI ISI TEKS CERITA RAKYAT DI SMP N 32 SEMARANG - Sutrisno, Muhammad Agus (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2018)
Retelling folklore is one of the Java language learning in class VII. The problem that existed in SMP N 32 Semarang is the interference of code or the insertion of Indonesian language into the Java language. The purpose of this study is to know the form or form that accompanied the functions and factors that influence the interference of the existing code in the activities of retelling the folklore. The approach used is qualitative approach. Data collection techniques used documentation techniques, references, interviews and questionnaire dissemination. Data analysis technique used in this research is descriptive analysis technique transcript retelling and descriptive percentage of questionnaire. The results showed that the mixed form with the function there are three. The first is the form of vocabulary, the repetition of words, and the last phrase form. Factors that influence the interference of the code in the activities of telling the folklore that is the habit that comes from the background of the family environment and school environment. Both of these factors become the cause of code interference in the activity of retelling the text of folklore.